1955
DOI: 10.1017/s0021859600045160
|View full text |Cite
|
Sign up to set email alerts
|

The effect of environmental temperature and humidity on the rectal temperature of calves

Abstract: 1. The rectal temperatures of three 4-month-old Ayrshire bull calves were measured in individual 6 hr. daily exposures to 15, 20, 25, 30, 35 and 40° C. dry-bulb temperature at low humidity (17 mg./l. absolute humidity) and to 30, 35 and 40° C. at high humidity (7 mg./l. saturation deficit). The experiments on each animal lasted 45 consecutive days and consisted of five replications of these nine environmental conditions. Measurements of rectal temperature were made every 5 min.2. The rectal temperatures of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1

Year Published

1959
1959
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 8 publications
5
32
1
Order By: Relevance
“…6) gradually rose from 6 a.m. to a maxrimum of 39.88°C at 6 p.m. then declined to a low of 39.45°C at 4 a.m. A similar pattern was observed in the fasted animals exrcept that the maximum temperature was reached 2 hr earlier, at 4 p.m., and the minimum temperature 2 hr later, at 6 a.m. These results are in close agreement with those of Beakley &; Findlay (1955b) and of Quartermain (1962).…”
Section: Short Term Variations In Temperaturesupporting
confidence: 90%
“…6) gradually rose from 6 a.m. to a maxrimum of 39.88°C at 6 p.m. then declined to a low of 39.45°C at 4 a.m. A similar pattern was observed in the fasted animals exrcept that the maximum temperature was reached 2 hr earlier, at 4 p.m., and the minimum temperature 2 hr later, at 6 a.m. These results are in close agreement with those of Beakley &; Findlay (1955b) and of Quartermain (1962).…”
Section: Short Term Variations In Temperaturesupporting
confidence: 90%
“…Finally, the late afternoon rise in body temperature was in accord with observations made in similar climatic circumstances (Quinlan & Mare, 1931;Hafez et al 1956). Beakley & Findlay (1955) also recorded a rise in body temperature of calves subjected to constant temperature and humidity in a psychrometric chamber. They considered the rise was of physiological origin since it was independent of experimental treatment.…”
Section: Body Temperaturesupporting
confidence: 86%
“…Magnitude of the diurnal fluctuation in body temperature is a reflexion of heat tolerance (Beakley & Findlay, 1955). Body temperature tended to be maximal at 1.0 p.m. (Appendix 3).…”
Section: Body Temperaturementioning
confidence: 99%
“…Kendall (1947) and Beakley and Findlay (1953) had already discussed the importance of changes in rectal temperature in the middle of the twentieth century. They suggested that measurement of the normal range of diurnal fluctuations could be a valuable indication of the ability of bovine calf support on thermal stress.…”
Section: Resultsmentioning
confidence: 99%